1996
DOI: 10.1111/j.1365-3040.1996.tb00001.x
|View full text |Cite
|
Sign up to set email alerts
|

The onset of sucrose accumulation in cold‐stored potato tubers is caused by an increased rate of sucrose synthesis and coincides with low levels of hexose‐phosphates, an activation of sucrose phosphate synthase and the appearance of a new form of amylase

Abstract: These experiments investigate events involved in triggering sugar accumulation in the cold in tubers of Solanum tuberosum L. cv. Desirée. Sugar content, 14C‐glucose metabolism, metabolite levels and activities of sucrose phosphate synthase (SPS) and starch‐degrading enzymes were followed after transfer to 4°C. (i) Net sucrose accumulation began between 2 and 4 d. By 10 d, reducing sugars were also increasing. From 20 d onwards, sugar accumulation slowed. Sucrose fell, but reducing sugars continued to increase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
64
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
(43 reference statements)
13
64
0
4
Order By: Relevance
“…La mayor conversión de almidón a azúcares solubles se debe a la acción de las giberelinas (GA) cuya síntesis puede ser estimulada por bajas temperaturas, estas sintetizan enzimas hidrolí-ticas, principalmente α-amilasa (Davies, 2004) isoamilasa, b-amilasa, a-glucosidasa y almidón fosforilasa (Cochrane et al, 1991;Cottrell et al, 1993;Claassen et al, 1993;Hill et al, 1996;Nielsen et al, 1997) encargadas de la degradación del almidón. Simultáneamente, los niveles de ABA disminuyen con el incremento en los niveles de frío y se ha encontrado que en bulbos de L. rubellum, almacenados a 4°C, la concentración de este inhibidor del crecimiento disminuye a medida que la vernalización aumenta (Rong-Yan et al, 2006) y también coincide con los estudios en Polianthes tuberosa (Nagar, 1995) y Allium wakegi ( Yamaz ak i et al, 2002).…”
Section: Tabla 2 Análisis De Correlaciones De Pearson Entre Variablesunclassified
“…La mayor conversión de almidón a azúcares solubles se debe a la acción de las giberelinas (GA) cuya síntesis puede ser estimulada por bajas temperaturas, estas sintetizan enzimas hidrolí-ticas, principalmente α-amilasa (Davies, 2004) isoamilasa, b-amilasa, a-glucosidasa y almidón fosforilasa (Cochrane et al, 1991;Cottrell et al, 1993;Claassen et al, 1993;Hill et al, 1996;Nielsen et al, 1997) encargadas de la degradación del almidón. Simultáneamente, los niveles de ABA disminuyen con el incremento en los niveles de frío y se ha encontrado que en bulbos de L. rubellum, almacenados a 4°C, la concentración de este inhibidor del crecimiento disminuye a medida que la vernalización aumenta (Rong-Yan et al, 2006) y también coincide con los estudios en Polianthes tuberosa (Nagar, 1995) y Allium wakegi ( Yamaz ak i et al, 2002).…”
Section: Tabla 2 Análisis De Correlaciones De Pearson Entre Variablesunclassified
“…Vol. 11 3 , 1997 Isherwood (1975) and Hill et al (1996) found no effect of storage temperature on phosphorylase activity, and Sowokinos et al (1985), who did report a selective increase in phosphorylase in the sweetening tuber tissues, found no changes in amylase activity. These inconsistencies might be due to differences between cultivars.…”
mentioning
confidence: 97%
“…Cold sweetening is of commercial interest, since high sugar content will result in a poor-quality product when the tubers are used for fries and chips. Recently, it was shown that the accumulation of sugars is due to a specific activation of Suc synthesis by up-regulation of SUC-P synthase (Hill et al, 1996). Along with the activation of Suc synthesis, a new amylolytic activity also induced in the cold-stored tubers was discovered.…”
mentioning
confidence: 99%
“…This could be sufficient for an increase in sucrose production in order to meet the elevated C demand of the mycorrhizal sink. An increase of the SPS activation state is mediated by reversible dephosphorylation of the enzyme protein (Huber & Huber, 1996) and occurs in a range of conditions such as low temperature (Hill et al, 1996), water and osmotic stress (Huber & Huber, 1996), and high light intensity (Stitt et al, 1988), all conditions which require increased sucrose production. The protein kinase involved in the modulation of SPS activation state, in turn, is also regulated, for example in spinach (Huber & Huber, 1996) as well as in spruce and aspen (A.…”
Section: Carbohydrate Metabolism In Shootsmentioning
confidence: 99%